Effect of food experience on overall satisfaction: comparison between first-time and repeat visitors to Malaysia - Roozbeh, B. H.; Ng, Siew Imm; Boo, Huey Chern (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The attractiveness of food as tourism product has partly derived from the gastronomic aspect. The ingredients, the preparations, the end products, and the eating circumstances are cultural, educational, and entertaining. However, there is little research empirically demonstrates if there is a difference between first-time and repeat visitors in terms of food experience at destination, or how the various food experience attributes influence visitors’ overall satisfaction while visiting a destination. Hence, this study was undertaken to address the gap. Data were collected via on-site survey questionnaire administrated to a random sample of visitors at the Kuala Lumpur International Airport (KLIA) and various touristic areas around Kuala Lumpur. The results indicated significant differences between first-time and repeat visitors in terms of their food experience. In addition, multiple regression analysis revealed that traditional food preparation was an important factor to tourists’ overall satisfaction for both first-time and repeat visitors. In sum, the study is the first to examine the effect of food experience attributes on first time and repeat visitors separately.